2023
DOI: 10.3390/app13031303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Common Treatments Used for Vairimorpha (Nosema) spp. Control

Abstract: Vairimorpha (formerly Nosema) apis and V. ceranae are microsporidian pathogens that are of concern for managed honey bee colonies. Multiple treatments have been proposed to be effective in reducing the prevalence and intensity of Vairimorpha spp. infections. Here, we test the efficacy of these products in one lab-based experiment and three field experiments. In the lab experiment, we found no reductions in Vairimorpha spp. prevalence (proportion of individuals infected with Vairimorpha spp.) or intensity (numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
7
2
Order By: Relevance
“…The clinical significance of heavy infection (25–50 million spores per bee) of ~20% of the colonies in the untreated group is unclear and should be investigated, but they could potentially be a source of infection for the adjacent colonies [ 35 ]. Contrary to our study, Prouty et al [ 54 ] reported higher spore loads in spring in fumagillin-treated colonies than in controls. The authors discussed fumagillin causing an imbalance in the gut microbiome and hence diminishing honey bee resilience towards Vairimorpha infections, increasing pathogen prevalence over time in treated colonies [ 54 , 55 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of heavy infection (25–50 million spores per bee) of ~20% of the colonies in the untreated group is unclear and should be investigated, but they could potentially be a source of infection for the adjacent colonies [ 35 ]. Contrary to our study, Prouty et al [ 54 ] reported higher spore loads in spring in fumagillin-treated colonies than in controls. The authors discussed fumagillin causing an imbalance in the gut microbiome and hence diminishing honey bee resilience towards Vairimorpha infections, increasing pathogen prevalence over time in treated colonies [ 54 , 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our study, Prouty et al [ 54 ] reported higher spore loads in spring in fumagillin-treated colonies than in controls. The authors discussed fumagillin causing an imbalance in the gut microbiome and hence diminishing honey bee resilience towards Vairimorpha infections, increasing pathogen prevalence over time in treated colonies [ 54 , 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Significant attention is paid to the application of Good Beekeeping Practices as a form of prevention (Formato et al 2022). However, while these methods yield some results, they still prove insufficient (Huang et al 2013, Holt and Grozinger 2016, Garrido et al 2023, Lang et al 2023, Prouty et al 2023). There is a pressing need for further research on N. ceranae , especially in the context of its effective control strategies that consider the microbiological safety of the hive products (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest an alternative way to control N. ceranae in honey bees using propolis collected from A. mellifera hives and extracted with suitable concentrations (50 and 75%) of propolis. This is especially important given the relative inefficacy of various controls available to treat N. ceranae infection in honey bees [70]. Admittedly, more work is needed before this treatment recommendation can be made.…”
Section: Discussionmentioning
confidence: 99%